IMPLEMENTATION OF VILLAGE FINANCIAL SYSTEM APPLICATION (SISKEUDES) TOWARDS TRUSTWORTHY GOVERNMENT IN MATANSALA VILLAGE AND TUDUA VILLAGE, BUNGKU TENGAH DISTRICT, MOROWALI REGENCY, CENTRAL SULAWESI PROVINCE - Setiawati Purwa Ningsih (Alqaprint Jatinangor, 2024)
The primary focus of this study is to examine and evaluate the Village Financial System Application (SISKEUDES), identify the factors influencing its implementation, and determine strategies to effectively utilize the SISKEUDES application to achieve reliable governance in Matansala and Tudua Villages, Bungku Tengah District, Morowali Regency, Central Sulawesi Province. This research is grounded in Indrajit's theories regarding the essential elements for the successful implementation of e-government and the factors impacting its execution, utilizing ASOCA analysis and litmus tests to develop strategies. Data collection involved observations, interviews, and gathering relevant documents on the use of the Village Financial System (SISKEUDES) in achieving trustworthy governance in Matansala and Tudua Villages, Bungku Tengah District, Morowali Regency, Central Sulawesi Province. Findings revealed that the application of SISKEUDES in these villages has not yet reached its full potential. Despite the availability of adequate facilities and infrastructure, human resource capabilities remain limited. Additionally, uneven comprehension among apparatus resources regarding the SISKEUDES application has led to the responsibility for its implementation being concentrated on specific individuals. Based on the ASOCA analysis and litmus test, several critical strategies were identified: providing technical guidance to village officials to enhance their skills; establishing rewards for village governments that implement the SISKEUDES application effectively and consistently to boost performance; improving coordination and communication between central and regional governments regarding application and oversight of SISKEUDES; conducting community outreach to promote understanding of village financial management and the benefits of the SISKEUDES application; increasing public awareness of regional regulations; and empowering rural communities through socialization efforts about adapting to changing times.